PENANDATANGAN MOU DAN KEGIATAN DONOR DARAH CIVITAS AKADEMIKA SEKOLAH TINGGI ILMU ADMINISTRASI BENGKULU DENGAN PALANG MERAH INDONESIA PROVINSI BENGKULU - Zetia Wijayanti; Herlinda Reski; Ameitha Pratiwi; Nurmailiza Nurmailiza; Yuli Yusnita (STIA Bengkulu, 2023)
MoU or memorandum of understanding is a memorandum of understanding, memorandum of understanding, cooperation agreement, or preliminary agreement. This term is actually not known in the Civil Code (KUHPer). However, in practice Memorandums of Understanding are always drawn up primarily for business contracts and are based on Article 1338 of the Criminal Code. The purpose of the MoU or Memorandum of Understanding made by STIA Bengkulu and PMI Bengkulu Province is to enter into a legal relationship as a letter made by one of the parties whose contents contain a will. The letter is addressed to other parties involved in the agreement. Blood donation is an activity of someone who voluntarily donates blood for the benefit of humanity. The purpose of carrying out this blood donor activity is to create a sense of solidarity among people, increase satisfaction with health services, assist the government in providing blood needs for healthy people, and overcome the impact of the spread of disease. Blood donation activities carried out by a person are considered very important, because the need for blood in the Blood Transfusion Unit of the Indonesian Red Cross, hereinafter written as UTD PMI in Bengkulu City, has only been fulfilled around 50% of the existing need, especially for referrals from several private public hospitals and private hospitals. Regional General Hospital.